Գեներալ Վասիլ Բեհբութով - Հովհաննիսյան, Հայկազ (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
Генерал Василий Осипович Бебутов (1791-1857) вписал блестящие страницы в летопись русского военного искусства и был представлен почти ко всем высшим наградам русской армии. Во время Крымской войны получив известие о победе русских войск в Кюрукдаринском сражении в 1854 г., император Николай наградил генерала Бебутова орденом Андрея Первозванного, которым в генерал-лейтенантском чине в России еще никто не был награжден. Увековечив свое имя на полях сражений, генерал Бебутов навсегда остался и в памяти армянского народа. The article is devoted to the military leadership activities of the outstanding Armenian general Vasil Osipovich Bebutov (1791-1857) and highlights his decisive role in the victories of the Russian army. General Bebutov wrote glorious pages in the annals of Russian military art, received almost all the highest awards of the Russian army. So, having received the news of the victory of the Russian troops in the battle of Kurukdara in 1854 during the Crimean War, Emperor Nicholay awarded General Bebutov with the Order of Andrey Pervozvanny, which no one had ever received in the rank of a General-Lieutenant in Russia. General Bebutov’s name immortalized on the battlefields remained in the memory of the Armenian nation too.
Keywords: Պատմություն; Կենսագրություն